220k views
3 votes
If h(z)=2z2-5z+7, find h(3c)

User Tronman
by
4.6k points

2 Answers

4 votes

See attachment for math work and answer.

If h(z)=2z2-5z+7, find h(3c)-example-1
User Svetlin Mladenov
by
5.1k points
4 votes

Answer: h(3c) = 18c2 - 15c + 7

Explanation:

h(z) = 2z2 - 5z + 7

To find h(3c), replace each z with 3c.

h(3c) = 2(3c)2 - 5(3c) + 7

Now just simplify.

h(3c) = 2(9c2) - 5(3c) + 7

h(3c) = 18c2 - 15c + 7

User CampbellMG
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.